How do Worry, Self-efficacy, and Coping Interact? Examining Chinese tourists to Australia. Issue 3 (1st October 2016) - Jin, Xin; Wu, Lei; Becken, Susanne; Ding, PeiYi
ABSTRACT: The current growth in Chinese outbound tourism is phenomenal, yet relatively little research has paid heed to issues related to how Chinese tourists overcome challenges before and during their trips. This study surveyed 463 Chinese tourists in Queensland, Australia to explore Chinese outbound tourists' levels of general and travel planning self-efficacy, worry, and coping, and examine the relationships among these constructs. Results show that the more tourists worry, the more they need to cope emotionally. Findings also suggest that measuring travel planning self-efficacy is relevant, as it significantly reduces worry and enhances task-oriented coping among Chinese tourists.